China’s government and companies’ strategic communications and grass-roots lobbying strategies in Africa in the digital age: a case study on China’s Confucius Institutes - (:unkn) unknown (My University, 2017)
This thesis focuses on China’s hybrid lobbying strategies (economic and cultural, hard and soft power) in the sectors of media and telecommunication in Africa, particularly in Kenya and South Africa. It intends to analyse changing Chinese soft power influence strategies in the digital and social media age. I rely on different perspectives and theoretical approaches: public policies cognitive analysis, media framing effects on political debates, critical analysis of the uses of information and communication tools in different socio- historical backgrounds, prospective analysis of PR techniques evolution (Davidson, 2016; Olsson & Eriksson, 2016; Yeomans, 2016; Kantola, 2016; Bernays, 2013; Berg, 2009). We mean to examine the innovative way in which the Chinese “party-state” spreads a certain vision of its culture and ideology on the African continent in order to promote its economic interest. This grass-roots lobbying (Barnes & Balnave, 2015; Schneider, 2015; Jalali, 2013; Reddick & Norris, 2013) can be described accurately with the metaphor of the Trojan horse.As the essential destination of the “21st Century Maritime Silk Road”, the official ways to name Chinese international relations’ strategy, Kenya has become a hub for China. China’s cultural institutions opened their first African Confucius Institute there. Being one of the members of BRICS, South Africa also grew into the business centre of China in Africa. Many important branches of Chinese Telecom companies are based in the country. It seems that these institutions, no matter public or private, were eventually being an essential channel for China’s local PR actions.As the core channels of “soft power”, culture and knowledge encapsulate values, ideologies and beliefs (Desmoulins & Huang, 2017; Gupta, 2013; Martel, 2013; DeLisle, 2010; Courmont, 2009; Bläser, 2005; Keohane, Jr, & Keohane, 1998; Nye, 2006, 2004, 1991). China’s cultural
Keywords: African Research